Masson’s Tumor of the Hand: An Uncommon Histopathological Entity - Parviz Mardani; Amir Askari; Reza Shahriarirad; Keivan Ranjbar; Amirhossein Erfani; Mohammad Hossein Anbardar; Shirin Moradmand (Case Reports in Pathology)
Masson’s tumor or Masson’s hemangioma, more precisely termed intravascular papillary endothelial hyperplasia (IPEH), is an uncommon benign vascular lesion of the skin and subcutaneous tissues which can be frequently confused with angiosarcoma. Although relatively rare, its accurate diagnosis is essential since it can clinically be similar to both benign and malignant lesions. We present a 39-year-old man with a round bulging arising from the left palm side of the hand with gradual growth in the last 5 months and on and off tenderness. The microscopic section demonstrated the papillary proliferation of endothelial cells in favor of Masson’s hemangioma, which was sufficiently treated with excision alone.